Zika Virus as Oncolytic Therapy for Brain Cancer: Myth or Reality? - Su, Kar Yan; Balasubramaniam, Vinod R. M. T. (Frontiers in Microbiology, 2019)
The ability of self-replicating oncolytic viruses (OVs) to preferentially infect and lyse cancer cells while stimulating anti-tumour immunity of the host strongly indicates its value as a new field of cancer therapeutics to be further explored. The emergence of Zika virus (ZIKV) as a global health threat due to its recent outbreak in Brazil has caught the attention of the scientific community and led to the discovery of its oncolytic potential for the treatment of glioblastoma multiforme (GBM), the most common and fatal brain tumour with poor prognosis. Herein, we evaluate the neurotropism of ZIKV relative to the receptor tyrosine kinase AXL and its ligand Gas6 in viral entry and the RNA-binding protein Musashi-1 (MSI1) in replication which are also overexpressed in GBM, suggesting its potential for specific targeting of the tumour. Additionally, this review discusses genetic modifications performed to enhance safety and efficacy of ZIKV as well as speculates future directions for the OV therapy.